7th International Conference on Clinical Neonatology—Selected Abstracts 2018
DOI: 10.1055/s-0038-1647092
|View full text |Cite
|
Sign up to set email alerts
|

Low Transfer of Tacrolimus and Its Metabolites into Colostrum of Graft Recipient Mothers

Abstract: Currently, the majority of neonates born to organ recipient mothers on chronic immunosuppressive therapy are formula fed. However, over the past few years, evidence has grown, suggesting that breastfeeding might be possible and beneficial. We designed a study assessing the transfer of tacrolimus into the colostrum of posttransplant mothers. We assessed the amount of tacrolimus and its metabolites, M-1 and M-3, that would be ingested by the breastfed neonates. Concentrations of tacrolimus and its metabolites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…62,64 Kociszewaska-Najman et al measured the concentrations of the Tac metabolites 13-O-demethyl tacrolimus (13-DMT) and 15-O-demethyl tacrolimus (15-DMT) in cord blood. 65 The mean concentration of Tac, 13-DMT, and 15-DMT in cord blood did not differ from that in fetal venous blood. Zheng et al 59 observed no difference in the primary Tac metabolite concentrations between the arterial and venous umbilical cord blood.…”
Section: Pharmacokinetics Of Tac Pharmacokinetics In the Mothermentioning
confidence: 75%
See 4 more Smart Citations
“…62,64 Kociszewaska-Najman et al measured the concentrations of the Tac metabolites 13-O-demethyl tacrolimus (13-DMT) and 15-O-demethyl tacrolimus (15-DMT) in cord blood. 65 The mean concentration of Tac, 13-DMT, and 15-DMT in cord blood did not differ from that in fetal venous blood. Zheng et al 59 observed no difference in the primary Tac metabolite concentrations between the arterial and venous umbilical cord blood.…”
Section: Pharmacokinetics Of Tac Pharmacokinetics In the Mothermentioning
confidence: 75%
“…Tac concentrations in breast milk were reported to range between 0.0038 and 3.219 ng/ mL. 47,57,59,65,[115][116][117] Milk-to-whole-blood and milk-toplasma ratios were 0.08-0.23 115,116 and 0.12-0.5, 47,59,117 respectively. Zheng et al investigated Tac excretion into breast milk over a 12-hour steady-state dosing interval in one patient.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
See 3 more Smart Citations